Kesenjangan Perencanaan dan Realisasi Anggaran Pendidikan di Kota Surabaya: Kajian Faktor Penyebab dan Implikasi Kebijakan Melalui Studi Literatur - Yudiansyah, Indira Ardina; Putri, Marshanda Ika Amelia; Fanida, Eva Hany; Fitrie, Revienda Anita (Indo-MathEdu Intellectuals Journal, 2026)
The management of education budgets is a key issue in the management of regional finances because it directly affects the equitable distribution of access to and quality of education. This study aims to analyse the regulatory framework for education funding, examine the allocation and implementation of education budgets in Surabaya based on previous research findings, identify the factors causing the discrepancy between planning and budget implementation, and formulate policy recommendations for improvement. This study uses a systematic literature review method to analyse 25 sources in the form of accredited journal articles, official government reports, audit results, and related regulations published between 2017 and 2025. Data were analysed using content analysis and narrative synthesis techniques. The results of the study show that while Surabaya consistently allocates more than 20% of its budget to education, there is still a significant gap between planning and implementation, particularly in capital spending and earmarked funds. This gap is influenced by the limited capacity of educational institutions to plan, the complexity of procurement procedures, delayed disbursement of funds, weak monitoring and evaluation systems, and external fiscal policy dynamics. This study emphasises the importance of strengthening the system for planning and controlling education spending in a coordinated manner